DETERMINAN KEJADIAN DIARE DAN MALARIA DI DESA GUNTURU KABUPATEN BULUKUMBA (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2022)
Health development towards a healthy Indonesia in 2025 is by increasing awareness, willingness and ability to live healthy for everyone so that the highest level of public health can be realized, which is marked by the behavior of the population in a healthy environment, having the ability to reach quality health services, fairly and equitably, and have the highest degree of health. The purpose of this study was to determine the determinants of diarrhea and malaria incidence in Gunturu, Bulukumba Regency. This type of research is a quantitative study with an observational analytic approach using a cross sectional study. Data were collected through a questionnaire distributed in Gunturu, Hero Lange-Lange District, Bulukumba Regency. Total respondents were 2377 individuals. The sampling technique used purposive sampling technique. The results showed that there was a relationship between washing hands with soap and the incidence of diarrhea in Gunturu with a P value of 0.003. Meanwhile, there is no relationship between the behavior of using bed nets without or with insecticides and the use of repellents and the incidence of malaria in the community of Gunturu, Bulukumba Regency.